Experimental investigation of the effects of red blood cell aggregation on blood flow - Theodorou Elena (Τμήμα Μηχανολόγων Μηχανικών και Επιστήμης και Μηχανικής Υλικών, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2016)
Two-phase fluids consist of a dispersed phase suspended in a continuous medium with the former having the form of cells, particles, liquid droplets or gas bubbles. Understanding multiphase flows is important since they occur in many areas such as biological systems and industrial applications. Blood is a complex fluid which consists of various cells, proteins and other macromolecules. The main constituent of blood is the red blood cell (RBC) which accounts for approximately the 45% of the fluid at normal conditions and therefore blood can be approximated as a two phase fluid. The flow of blood at low shearing flow conditions is dominated by the effects of RBC aggregation (a reversible clustering of the cells) and other secondary effects such as network formation. This project aims at studying blood flow in simple shearing flows and to analyze the changes in the flow characteristics (velocity, shear rate profiles, etc.) caused by the phenomenon of RBC aggregation. More specifically this project aims at studying specific parameters affecting the flow properties of blood, measuring the mean velocity of RBCs and how the velocity is affected by the phenomenon of aggregation and studying the various aggregation states, and how the shear forces affect the aggregation. Specialized software packages and particle tracking techniques will be used for the analysis of the flow with the prospect of modeling the observed flow behavior. The main outcome of this present work is that the flow of blood at low shearing flow conditions is dominated by the effects of RBC aggregation and other secondary effects such as network formation. Analyzing the changes in the velocity profiles caused by the phenomenon of RBC aggregation and cell sedimentation can be support that the aggregation affects blood flow; in aggregative case of D70 and D2000 is observed medium for D70 and high aggregation for D2000 at low shear rates.
Keywords: Blood; Cells; Proteins; Macromolecules; Red blood cell (RBC)